Varietal resistance of pea to powdery mildew in dry temperate zone of Himachal Pradesh - and R.S. JAMWAL, B.R. THAKUR, A.S. KAPOOR (Indian Phytopathology, 2002)
In 1992-93 pea lines were tested for resistance to powdery mildew disease caused by Erysiphe pisi in Himachal Pradesh, India. Of 86 lines tested, 7 had a disease score of